Special Issue Editors' Introductory Note: The Why and How of the Decolonization Discourse - Bagele Chilisa; Nicole Bowman (The Evaluation Center at Western Michigan University, 2023)
The theme of the special issue decolonizing evaluation: towards a fifth paradigm,  an initiative of the International Evaluation academy (IEA), was inspired by the concerns that while evaluation reports largely tell stories of success, on the ground there is minimal change, communities remain impoverished, interventions cause harm to the environment and evaluation allow that to happen.